ANTIMICROBIAL ACTIVITY OF METHANOLIC EXTRACT OF LUDWIGIA PARVIFLORA L. AGAINST STANDARD BACTERIAL STRAINS AND COMPARISON OF ITS ACTIVITY WITH THAT OF STANDARD ANTIBIOTICS - GEORGE, SHIBU; JOY, MEVLIN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to evaluate the antimicrobial activity of methanolic extract of Ludwigia parviflora L. using standard bacterial strains and compare its activity with that of standard antibiotics. Methods: The antibacterial activity and antibiotic susceptibility tests were done by disk diffusion method using MTCC bacterial strains. Results: The study revealed that the methanolic extract of the whole plant of L. parviflora L. was effective to inhibit the growth of Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Escherichia coli. Among the tested strains, S. aureus, P. aeruginosa, K. pneumoniae, and E. coli were more susceptible to the methanolic extract of L. parviflora than the commonly using antibiotic tetracycline 30 mcg. The activity of methanolic extract was also higher than the activity of gentamicin 10 mcg against the P. aeruginosa. Conclusion: The study concluded that the crude methanolic extract of the whole plant of L. parviflora L. is a good source for antibacterial agent against S. aureus, P. aeruginosa, K. pneumoniae, and E. coli. Hence, this plant can be used as a natural alternative to the common antibiotics such as gentamicin and tetracycline against common bacterial infections after validating its pharmacological and toxicological activities.